2017
DOI: 10.5902/2236583423332
|View full text |Cite
|
Sign up to set email alerts
|

A Mastectomia E Suas Repercussões Na Vida Afetiva, Familiar E Social Da Mulher

Abstract: RESUMOObjetivos: Identificar os problemas enfrentados pela mulher mastectomizada na vida afetiva, familiar e social. Metodologia: Realizou-se um estudo descritivo de caráter qualitativo, com 10 mulheres mastectomizadas, participantes do grupo de apoio Renascer. A coleta de dados deu-se por meio de entrevista, tendo como instrumento um questionário elaborado pela pesquisadora. Os dados foram posteriormente analisados de forma qualitativa conforme proposta de sistematização de Minayo. Resultados: Foram identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 2 publications
0
2
0
11
Order By: Relevance
“…17 Surveys conducted with women who underwent hysterectomy showed that the partners showed support during the procedure, which conveys safety to the partner and proved to be a positive Sexuality of hysterectomized women Schmidt A, Sehnem GD, Cardoso LS, Quadros JS, Ribeiro AC, Neves ET experience that facilitated the experience of gynecological surgery. 18,19 This opportunity, through gynecological surgery, to reevaluate feelings and attitudes within the marital relationship may be associated with the quality of the couple's relationship. 19 In addition, this reiterates that the value that the organ removed has for women is historically based on social and cultural constructions, which delimited roles and obligations inherent to each sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Surveys conducted with women who underwent hysterectomy showed that the partners showed support during the procedure, which conveys safety to the partner and proved to be a positive Sexuality of hysterectomized women Schmidt A, Sehnem GD, Cardoso LS, Quadros JS, Ribeiro AC, Neves ET experience that facilitated the experience of gynecological surgery. 18,19 This opportunity, through gynecological surgery, to reevaluate feelings and attitudes within the marital relationship may be associated with the quality of the couple's relationship. 19 In addition, this reiterates that the value that the organ removed has for women is historically based on social and cultural constructions, which delimited roles and obligations inherent to each sex.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 This opportunity, through gynecological surgery, to reevaluate feelings and attitudes within the marital relationship may be associated with the quality of the couple's relationship. 19 In addition, this reiterates that the value that the organ removed has for women is historically based on social and cultural constructions, which delimited roles and obligations inherent to each sex. 4 Thus, female nature has as its main basis biological facts that occur in the woman's body, such as the ability to generate, give birth, and breastfeed, as well as period.…”
Section: Discussionmentioning
confidence: 99%
“…A forma como a mulher vivencia o adoecimento por câncer mamário afetará suas relações sociais em geral, repercutindo em estados de depressão e podendo desencadear modificações nos hábitos de vida 4,6,7,8 . Com isso, após a confirmação do diagnóstico, a mulher se depara com dois problemas: o medo do câncer e seu estigma de doença terminal, e a possível mutilação de uma parte exclusiva do corpo feminino 6,9,10,11 .…”
Section: Introductionunclassified
“…Seus resultados -associados ou não a tratamentos complementares -podem causar efeitos colaterais, afetando-as física, social e emocionalmente 4,12,14 . Os efeitos psicológicos gerados pelo impacto do diagnóstico e dos tratamentos provocam mudanças na vida dessas mulheres que vão desde suas atividades diárias 7,14,15 e convívio social até sua sexualidade e percepção da própria imagem corporal 3,11,16 .…”
Section: Introductionunclassified
See 1 more Smart Citation